PERBANDINGAN PERATURAN TANDA TANGAN DIGITAL DI NEGARA JEPANG DAN NEGARA INDONESIA (STUDI PUTUSAN: NOMOR 61/PID/2017/PT YYK) - Millenia, Meisya; Pakpahan, Kartina; Sulistyawaty, Sri (Penerbit Lafadz Jaya, 2023)
Digital signatures are a substitute for manual signatures that are electronic and have the same function as manual signatures. However, the development of digital signatures has not yet been realized in the world of notarial services, especially in the creation of authentic deeds by notaries. This research uses a Normative Juridical approach. Data was collected through literature research and using qualitative and descriptive analysis. Conclusions from this research, the implementation of electronic digital signatures has been implemented in a number of authentic deeds, but not all are allowed to use digital signatures, some are required to still use hanko or signatures in the form of stamps made of wood. However, in Indonesia the implementation of digital signatures is still unclear, which is why currently digital signatures have been implemented, however, their use is only in documents in the form of personal identity such as Resident Identification Cards, Driving Licenses, etc and Legal sanctions for criminal acts of misuse of digital signatures in Indonesia include forgery of documents which can be charged under Article 263 paragraph (1) of the Criminal Code. The perpetrator is threatened with imprisonment for six years. In Japan, the crime of misuse of digital signatures is regulated in the Cybercrime Law which was passed in 2011 and the Act on Electronic Signatures and Certification Business Act No. 102. However, the penalties that may be applied depend on various factors, including the severity of the offense, the harm caused. The government's efforts to prevent the misuse of criminal acts of digital signature falsification are by strengthening the digital certification security system, conducting regular audits on services that use digital signatures, implementing effective reporting and following up on cases by providing strict sanctions to provide a deterrent effect at the perpetrator.